2004
DOI: 10.1111/j.1399-3038.2004.00190.x
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal skin reactivity to histamine in atopic children in Singapore: influence of specific sensitizations

Abstract: Histamine skin prick test (SPT) is used as the 'golden standard' for positive control in in vivo immediate type hypersensitivity testing. The skin reactivity to histamine can, however, be modulated by a bevy of extraneous factors. We aimed to define whether histamine skin reactivity in atopic children in Singapore is influenced by age, ethnic origin, gender, environmental exposure or specific sensitization patterns. A retrospective analysis of children, with specific aeroallergen sensitization (as measured by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 24 publications
0
12
1
Order By: Relevance
“…Previous studies have reported that histamine skin reactivity increases with allergic sensitization, along with the number of sensitized allergens [6,10,11,24,26]. Sex, parental allergy history, parental smoking status, allergic sensitization, and number of sensitized allergens were not associated with histamine skin reactivity in multivariate analysis.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Previous studies have reported that histamine skin reactivity increases with allergic sensitization, along with the number of sensitized allergens [6,10,11,24,26]. Sex, parental allergy history, parental smoking status, allergic sensitization, and number of sensitized allergens were not associated with histamine skin reactivity in multivariate analysis.…”
Section: Discussionmentioning
confidence: 48%
“…The study questionnaire was distributed, filled out by students and parents, and collected between October 15 and 30, 2010. Skin prick tests and physical examinations were carried out by trained nurses from November 8 to 11,2010. From a total of 687 first and second grade children from six elementary schools, 602 were included in the study.…”
Section: Study Populationmentioning
confidence: 99%
“…Although studies have shown that the magnitude of the SPT, for particular food allergens, has a good correlation with challenge‐derived hypersensitivity data [28], this correlation and the respective weal size thresholds have not been validated in Asian children. It seems likely, however, that threshold differences may exist, because we do know that average SPT responses to the histamine‐positive control show significant variations in our population [29], emphasizing the need for such local validation studies.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that age [1,2], immunotherapy [3], habitat [4] and menstrual cycle [5] influence the size of the prick. The more positive allergen skin prick tests, the bigger the histamine wheal [6,7]. In pollen-allergic patients, the sensitivity of the shock organ varies over the year [8], and probably also the skin sensitivity to the offending allergen, but to histamine as well to some degree, shows similar changes [9].…”
mentioning
confidence: 92%